Mother-fetus immunogenetic dialogue as a factor of progeny immune system development - L. A. Gerlinskaya; A. V. Varlachev; G. I. Krotov; G. V. Kontsevaya; M. P. Moshkin (Вавиловский журнал генетики и селекции, 2019)
Despite the advances in medicine, about 4 million children under the age of 6 months die annually around the world due to infection, which is 450 deaths per hour (UNISEF, 2009). The degree of development of the immune system of children born in time is determined by many factors, including the immunogenetic similarity or diﬀerence of mother and fetus organisms, which, in turn, is due to the genotypes of mating pairs, as well as the selection of surrogate mothers during in vitro fertilization. From our review of the literature, it follows that immunogenetic interactions of mother and fetus organisms, which occur at all stages of pre- and postnatal development, have a signifcant eﬀect on the resistance of oﬀspring to infections and allergens. Before implantation, the mother’s immune responses are formed under the inﬂuence of semen ﬂuid antigens, leukocytes and cytokines, as well as under the inﬂuence of the genes of the major histocompatibility complex, which are expressed in embryos at the stage of two cells. After implantation, transplacental transfer of immunoglobulins and immunocompetent cells becomes of immunomodulating importance. It is important to emphasize that, although substances with a high molecular weight usually do not pass through the placenta, this rule does not apply to immunoglobulin G (IgG), which, with a molecular weight of about 160 kDa, overcomes the transplacental barrier due to binding to the fetal Fc receptor. The level of IgG in newborns usually correlates with the level of maternal antibodies. During the period of natural feeding, the immune protection of newborns is provided by the mechanisms of innate immunity and the factors of humoral immunity of mothers. It has been shown that immunoglobulins from the milk of many animal species are transferred through the neonatal intestinal epithelium to the blood. Since breast milk contains large amounts of various immunoactive components, including proteins, cytokines, hormones, immunoglobulins, exosomes containing micro-RNA, and viable immune cells, the immunomodulating eﬀects of breast milk persist even after elimination of maternal immunoglobulins from the blood of the oﬀspring, up to maturation. Analysis of a large body of experimental data shows that the study of mechanisms of “motherfetus” and “mother-newborn” interactions are the basis of a knowledge base needed to fnd means of life-long directed modulation of the descendants’ immune status.